2013
DOI: 10.5230/jgc.2013.13.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Distal Gastrectomy in a Patient with Situs Inversus Totalis: A Case Report

Abstract: We report our experience with two cases of situs inversus totalis, both involving patients diagnosed with gastric cancer. These were a 52-year-old male with a preoperative staging of cT1bN0M0 and a 68-year-old male with a staging of cT2N0M0, both of whom underwent surgery. The former was found to have vascular anomalies in the preoperative computed tomography, so we performed a computed tomography angiography with three-dimensional reconstruction. Laparoscopy-assisted distal gastrectomy with Billroth I anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Previous studies have reported that the most important and confusing problem is vascular anomaly, and 3‐D‐CT angiography is helpful in resolving this problem . We also discussed the anatomical images obtained from 3‐D‐CT angiography, which showed that the present case had no anomaly of vessels other than complete reversal.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous studies have reported that the most important and confusing problem is vascular anomaly, and 3‐D‐CT angiography is helpful in resolving this problem . We also discussed the anatomical images obtained from 3‐D‐CT angiography, which showed that the present case had no anomaly of vessels other than complete reversal.…”
Section: Discussionmentioning
confidence: 67%
“…Four cases had clinical stage IA, and one had clinical stage IB disease. D1+ lymph node dissection and Billroth I reconstruction were performed in all five cases (Table ) , which were reported from Asia (three from Japan and two from Korea). Surgeons in these past cases in Japan performed surgery while standing opposite to their normal positions, whereas surgeons in the Korean cases stood in a normal position.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to prevent such intraoperative complications, we carefully analyzed this patient's anomalies in imaging findings and set up a surgical procedure modified for SIT. Min et al reported that 3D reconstruction images of CT are useful in understanding the vascular anatomy of patients with SIT 10 . We utilized 3D-CT images of the stomach and pancreas, as well as those of blood vessels to preoperatively simulate the positional relationships of these organs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of laparoscopic surgery for gastric cancer are increasing in accordance with good progress in laparoscopic procedures. Recently, seven cases of laparoscopic distal gastrectomy (LDG) for gastric cancer with lymphadenectomy in patients with SIT have been reported [5][6][7][8][9][10][11] . These studies suggest that laparoscopy is useful in surgery for patients with SIT.…”
mentioning
confidence: 99%
“…There have been some reports describing surgical procedures in patients with malignancy associated with CSI [ 2 6 ]. Several authors have reported difficulties with surgical procedures caused by the distinctive features of CSI, and some have mentioned that preoperative 3D-CT is very useful for assessing the structures of arteries and major organs in patients with CSI [ 5 7 ]. In our case, CT showed no major vascular abnormalities.…”
Section: Case Presentationmentioning
confidence: 99%